PERAN PENDAMPING DANA DESA DALAM PENGELOLAAN ANGGARAN DANA DESA DI DESA SALUTA KECAMATAN GALELA UTARA KABUPATEN HALMAHERA UTARA - LOBOR, NARWIN; OGOTAN, MARTHA; LONDA, VERY (Sam Ratulangi University, 2018)
he objective of the study was to explain the role of village fund supporters in the management ofvillage budget funds in Saluta Village, North Galela District, North Halmahera District. This study useddescriptive qualitative method. The role of village fund supporters in managing the village funding budgetis seen from three indiktaors namely planning, implementation, and monitoring. The research informantsare Village Head, Village Secretary, Village Treasurer, Head of Sub-District Coordinator Coordinator,Village Local Assistant Officer. Date collection using interview guides, observation study documentationwhile the analysis technique is done through the stages of data collection, data reduction, data presentation.Based on the results of data analysis, it is concluded that the role of village funding supporters in managingthe village budget funds in Saluta Village, Gaelautara District, North Halmahera Regency, is seen from theindicators of planning, implementation and monitoring has not been maximally implemented.Based on the result of the research, it is found that the role of the village fund counselor in managingthe village budget is not maximized so that it can be recommended suggestion: The companion mustunderstand the mechanism of the companion officer in seeing the priority of community needs. Villagecounseling officers should be people who have good skills in the aspects of knowledge / education (technicalskills specialist), experience, mental attitude, and have a commitment and high integrity in carrying outduties and functions as a companion; Village facilitators should further optimize their functions throughmonitoring the allocation of village funds in the development of village infrastructure Saluta done regularlyand periodically.Keywords: Roles, Assistance, Management, Village Funds.